Facile Synthesis of Graphene from Waste Tire/Silica Hybrid Additives and Optimization Study for the Fabrication of Thermally Enhanced Cement Grouts - Ilayda Berktas; Ali Nejad Ghafar; Patrick Fontana; Ayten Caputcu; Yusuf Menceloglu; Burcu Saner Okan (Molecules, 2020)
This work evaluates the effects of newly designed graphene/silica hybrid additives on the properties of cementitious grout. In the hybrid structure, graphene nanoplatelet (GNP) obtained from waste tire was used to improve the thermal conductivity and reduce the cost and environmental impacts by using recyclable sources. Additionally, functionalized silica nanoparticles were utilized to enhance the dispersion and solubility of carbon material and thus the hydrolyzable groups of silane coupling agent were attached to the silica surface. Then, the hybridization of GNP and functionalized silica was conducted to make proper bridges and develop hybrid structures by tailoring carbon/silica ratios. Afterwards, special grout formulations were studied by incorporating these hybrid additives at different loadings. As the amount of hybrid additive incorporated into grout suspension increased from 3 to 5 wt%, water uptake increased from 660 to 725 g resulting in the reduction of thermal conductivity by 20.6%. On the other hand, as the concentration of GNP in hybrid structure increased, water demand was reduced, and thus the enhancement in thermal conductivity was improved by approximately 29% at the same loading ratios of hybrids in the prepared grout mixes. Therefore, these developed hybrid additives showed noticeable potential as a thermal enhancement material in cement-based grouts.